Toward a Framework for Safeguarding Financial Stability. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper examines the emergence of financial stability as a key policy objective. It discusses the underlying trends in the financial system, as well as the role of finance in relation to money, the real economy, and public policy. Financial stability is defined in terms of its ability to help the economic system allocate resources, manage risks, and absorb shocks. Moreover, financial stability is considered a continuum, changeable over time and consistent with multiple combinations of its constituent elements. On the basis of these concepts, a framework is presented that comprises an encompassing analysis and assessment of financial stability, and maps out broad policy implications.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet